Urbanization and fertility rates in Ethiopia - Tadesse, Fanaye; Headey, Derek D. (International Food Policy Research Institute, 2012)
Fertility rates are important determinants of overall population growth and demographic transitions from high to low age dependency ratios. These in turn have important consequences for economic growth, poverty reduction, and improved health and nutrition outcomes. Ethiopia currently has one of the highest fertility rates in the world, although there are marked differences between rural and urban fertility rates. This paper explores the drivers of rural and urban fertility rates, including systematic tests of differences in key determinants. These further allow us to project fertility rates into the future based on alternative urbanization, economic growth, and education scenarios. Finally, we link these alternative projections with existing estimates of the benefits of fertility reduction on economic growth, nutrition, and poverty reduction.